2014
DOI: 10.2105/ajph.2013.301648
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Attributable Mortality Among American Indians and Alaska Natives in the United States, 1999–2009

Abstract: Proven strategies that reduce alcohol consumption and make the environment safer for excessive drinkers should be further implemented in AI/AN communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…12 American Indians and native Alaskans had a significantly higher mortality from chronic ALD compared with white people. 13 Recently, genome-wide association studies found that the patatinlike phospholipasedomain containing protein 3 (PNPLA3) gene is associated with increased hepatic fat content and an increased risk of developing both alcoholic and nonalcoholic fatty liver disease. 14 A meta-analysis found that the PNPLA3 polymorphism increases the risk of developing the entire spectrum of ALD and is associated with increased disease severity.…”
Section: Epidemiology Of Alcoholic Liver Diseasementioning
confidence: 99%
“…12 American Indians and native Alaskans had a significantly higher mortality from chronic ALD compared with white people. 13 Recently, genome-wide association studies found that the patatinlike phospholipasedomain containing protein 3 (PNPLA3) gene is associated with increased hepatic fat content and an increased risk of developing both alcoholic and nonalcoholic fatty liver disease. 14 A meta-analysis found that the PNPLA3 polymorphism increases the risk of developing the entire spectrum of ALD and is associated with increased disease severity.…”
Section: Epidemiology Of Alcoholic Liver Diseasementioning
confidence: 99%
“…For example, a recent report indicated that 8 th graders living on or near reservations report much higher rates of “gotten drunk” and “binge drinking” (18.5% and 18.3%, respectively) relative to national rates (4.9% and 7.1%, respectively) (Stanley, Harness, Swaim, & Beauvais, 2014). Also, the burden of alcohol-attributable deaths is high, with AI/AN persons having had a substantially higher rate of alcohol-attributable death than Whites from 2005 to 2009 in counties covered by the Indian Health Service (Landen, Roeber, Naimi, Nielsen, & Sewell, 2014). …”
mentioning
confidence: 99%
“…However, the proportion of these deaths with alcohol or drugs listed as a factor among rural and remote residents (14%) was less than half that of urban AN residents (32%). Alcohol or other drugs were a contributing factor for a much higher proportion of natural environment deaths among AN than AKWs, a pattern also documented in a national study of American Indian/Alaska Native and USW mortality [20]. Although commonly believed to warm the body, alcohol consumption has been demonstrated to lower core body temperature in cold weather conditions, thereby exacerbating hypothermia risk [12,13].…”
Section: Discussionmentioning
confidence: 96%